ASIAN GAMES 2014: IMPLEMENTASI BHINNEKA TUNGGAL IKA MELALUI OLAH RAGA - Ascosenda Ika Rizqi (Jurnal Civic Hukum, 2016)
Indonesia is a country that has a very high level of pluralism and a complex level of social plurality. The Indonesian nation has been aware of the diversity of languages, cultures, religions, ethnicities and ethnicities, the understanding of the value of Unity in Diversity in Indonesian society can be manifested integrally with the cooperation of all components of the nation, both by the government as the organizer of the country and each individual's private citizens. Asian Games is the biggest moment of the Asian nation, especially in the field of sports that have been held since the 1950s. The 2014 Asian Games is certainly not only a matter of sports from various branches, but for a moment as an Indonesian citizen there is certainly a spirit of unity in diversity in its implementation